Disseminated intravascular coagulation with positive D-dimer: a controversial clinical feature in severe congenital factor XIII deficiency in southeast Iran. Issue 8 (December 2016) - Naderi, Majid; Tabibian, Shadi; Menegatti, Marzia; Kalantar, Ebrahim; Kazemi, Ahmad; Zaker, Farhad; Dorgalaleh, Akbar
Abstract : Disseminated intravascular coagulation (DIC) is an extremely rare coagulopathy in the rare factor XIII (FXIII) deficiency. Compensated DIC occurs because of injuries that lead to systemic coagulation activation that is amplified by impaired fibrinolysis. This challenge translates into the widespread deposition of fibrin degradation products in the circulation. The aim of this study is to report three cases with severe FXIII deficiency who presented with DIC and positive D-dimer. Here we describe three patients affected by both FXIII deficiency and DIC; two girls aged 17 and 45 days and a 3.5-year-old boy. All patients had a positive family history for FXIII deficiency. Umbilical cord bleeding was the first presentation of FXIII deficiency in all of them, who presented also with ecchymosis; two of them had delayed wound bleeding. DIC occurred simultaneously with intracranial haemorrhage in two patients, whereas the third experienced DIC following extensive haematoma. D-dimer measured in all patients ranged between 5 and 20 μg/ml, whereas fibrinogen degradation product was between 4 and 8 μg/ml.